2012
DOI: 10.3354/meps09577
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the heat tolerance limits of two abundant Southern Ocean invertebrates

Abstract: While, in lower latitudes, population-level differences in heat tolerance are linked to temperature variability, in the Southern Ocean remarkably stable year-round temperatures prevail. Temporal variation in the physiology of Antarctic ectotherms is therefore thought to be driven by the intense seasonality in primary productivity. Here we tested for differences in the acute upper temperature limits (lethal and activity) of 2 Antarctic marine invertebrates (the omnivorous starfish Odontaster validus and the fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
1
27
1
Order By: Relevance
“…Several studies have suggested that measuring the righting time, how long it takes an individual to return to its normal orientation after having been disturbed, could provide a good indication of whether an individual is exhibiting a stress related response [24]–[28]. Such a stress response could be elicited by a variety of different mechanisms including the direct impacts of a physical or chemical change (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that measuring the righting time, how long it takes an individual to return to its normal orientation after having been disturbed, could provide a good indication of whether an individual is exhibiting a stress related response [24]–[28]. Such a stress response could be elicited by a variety of different mechanisms including the direct impacts of a physical or chemical change (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, a decreased AEC is indicative of stress in response to sublethal environmental changes 46 , although the lowest levels attained in the present study (≥0.90) are above the levels considered indicative of mild (0.5-0.75) or severe (~0.5) stress 47 . Buffering AEC could be achieved by short-term mobilization of ArgP, as shown in several situations of high ATP demand, such as intense muscular activity 34,48 , hypoxia 49 and hyperthermia 50 . Such a metabolic strategy seemed to occur in adult scallops in which ATP content was not altered at the expense of decreased levels of ArgP at 30 °C.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies of physiological capacities to respond to temperature stress in Antarctic marine species over recent decades on a very wide range of different taxa, including fish (e.g. Macdonald & Montgomery 1982, Hardewig et al 1999b, Hofmann et al 2000, Wilson et al 2001, Podrabsky & Somero 2006, Franklin et al 2007, Robinson & Davison 2008, Bilyk & DeVries 2011, Strobel et al 2012, Todgham et al 2017, molluscs (Peck 1989, Urban & Silva 1998, Clark et al 2008a,b, Morley et al 2010,b,c, Reed et al 2012, Reed & Thatje 2015, echinoderms (Stanwell-Smith & Peck 1998, Clark et al 2008b, Morley et al 2012b, amphipods (Young et al 2006a,b, Clark et al 2008b, Doyle et al 2012, Gomes et al 2013, Schram et al 2015b, isopods (Whiteley et al 1996, Robertson et al 2001, Young et al 2006a,b, Janecki et al 2010, brachiopods (Peck 1989, Peck et al 1997a, sponges (Fillinger et al 2013), and macroalgae or phytoplankton (Montes-Hugo et al 2009, Schloss et al 2012. There have also been many assessments of the effects of elevated temperature using a larger-scale approach, both experimentally and using field observations identifying multispecies response or evaluating community, ecosystem or overall biodiversity level responses (e.g.…”
Section: Rising Temperaturesmentioning
confidence: 99%